Profile of care given to patients with blunt chest injuries within the first 48 hours - E Nyangena (AOSIS, 2000)
This study was conducted in the trauma unit of a large academic hospital in Johannesburg, South Africa. The study aimed at describing the nature of care that patients with blunt chest injuries received during the first 48 hours after injury. A descriptive survey was chosen using retrospective and prospective record review to obtain data. The sample comprised 60 records of patients who were admitted to the hospital due to blunt chest injuries between January 1997 and June 1998. Descriptive statistics were used to present and analyse data. The study showed that: (i) Blunt chest trauma victims received a thorough initial assessment and care. No missed injuries were identified on subsequent assessment; (ii) More than half of the patients spent over one hour in the accident/emergency department before admission to the trauma ward or intensive care unit (ICU); (iii) Motor vehicle accidents (MVA) were the commonest cause of injury while pedestrian vehicle accidents (PVA) were often fatal; (iv) Nurses are good providers of care but poor in prescribing and documenting care; (v) Pain assessment and psychosocial care was often neglected; (vi) Less than half the patients developed complications during the first 48 hours; pain and pneumonia being the most common complications encountered.